Collection of Malting Barley Varieties in the Czech Republic in 2010 - Psota, Vratislav; Sachambula, Lenka; Kosař, Karel (BrewingScience, 2011)
The present study reviews changes in the requirements for malting quality and collection of malting barley varieties in the Czech Republic in 2010. It gives micromalting results and results of malt and wort analyses of 22 most widespread and new malting barley varieties registered in the Czech Republic. Varieties causing haze were withdrawn from the collection. The actual collection includes two groups of malting barley varieties. The varieties with high activity of hydrolytic enzymes and high attenuation and the varieties recommended for production of beer with the Protected Geographical Indication Czech Beer, i.e. varieties with lower degree of final attenuation, lower values of Kolbach index, friability, etc.